HIV prevention programs of nongovernmental organizations in Latin America and the Caribbean : the global AIDS Intervention Network project - Fernandez, M. Isabel...[et al.] (2005)
Describes HIV prevention programmes conducted by nongovernmental organizations that are meeting the challenge.